Learning communities - Hessenauer, Sarah; Simon, Shirley R. (Groupwork, 2014)
Learning communities are becoming increasingly common as a means of assisting incoming students with their transition to college. They have been shown to improve student retention, academic performance, and student-faculty relationships. Learning communities are prime examples of groupwork in action, and can provide opportunities for educators to teach and model social groupwork concepts and principles. This paper 1) defines and describes learning communities, 2) discusses the theoretical basis for the application of groupwork principles to the learning community experience, and 3) describes and assesses three years of experience with the application of groupwork principles in social work learning communities in an undergraduate university in the Midwestern United States.